Trading Information The City of Nuremberg and the Birth of a Latin Medical Weekly - Kinzelbach, Annemarie; Ruisinger, Marion Maria (Civic Medicine. Physician, Polity, and Pen in Early Modern Europe, 2020)
This chapter analyses the founding of Commercium litterarium, among the earliest weekly medical journals (1731–1745), aiming to determine what was distinctive and significant about this journal in the history of knowledge and what made it possible. Commercium litterarium accelerated and regularized “knowledge in motion.” This is why such an enterprise was the undertaking of a society of medical officers in a major trading city. Nuremberg’s system and forms of commerce and communication enabled and inspired the creation of the journal. Equally important was that Nuremberg’s physicians were not only competing practitioners, but sworn civic doctors who comprised an organized community, a Collegium medicum, with a broad public mission. The public they strove to transform through their enterprise of gathering and reading, selecting and rewriting, translating vernacular into Latin and distributing was continuous with this local one, yet much wider: it was the medical and scientific Republic of Letters.<br
CRIS-Team WoS Importer:2021-08-13